Pembangunan IKN dan perlindungan keanekaragaman hayati - Delphia, Risanti (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The Indonesian government has decided to relocate the capital from Jakarta to the Nusantara Capital in East Kalimantan. On the other hand, the capital development area is a center of ecosystems that serve as habitats for various animals and plants. This research aims to understand the changes in ecosystems and biodiversity protection in the new capital region of East Kalimantan. Methods: This research employs a literature review method to use previous references as a basis for understanding the phenomena under study. Additionally, ecological concepts and biodiversity are also utilized. Finding: This research finds that the process of relocating the capital will face issues involving social, economic, and environmental aspects. Since the beginning (2015-2019), East Kalimantan has been burdened with ecological problems, such as forest fires, thus the ecological burden of capital development cannot be avoided. Therefore, government capacity is needed to ensure the preservation of biodiversity. Conclusion: The development of the new capital must consider principles of conservation protection, life support systems, and sustainable utilization.